Características geográficas do Estado do Paraná frente aos desastres naturais - Gonçalves M.; Vizintim M. F.B. (Confins)
This study arose from the need for qualitative analysis of the geographical area components of the Paraná front of natural disasters, especially the urban floods, floods, mudslides and landslides. For this it applied the GTP concept in three times in trying to understand how is the role of nature and its forces as a source of natural hazardous events. As society behaves on these events, understanding how social dynamics, economic and cultural can be supported to stop, or at least mitigate, the intensity of these events, making the front of the source resource and revival through culture, symbols and traditions. The geosystem components considered in this study were: geology; relief; soils; climate; hydrography. As for the components of the territory are expressed in the Social Vulnerability Index, degree of urbanization, population density and analysis of transport and communication networks. The landscape components were materialized in historical, documentary, natural, archaeological and different traditional communities. Each GTP component provided elements capable of expressing the present phenomena in the analysis of space, generating subsidies for a thorough understanding of the risk of natural disasters in the State of Paraná.